Recommendations for Placement of Internships in Industry with the Distance from Average Solution (EDAS) method based on student scores - Tomy Satria Alasi; murdani murdani (INFOKUM, 2022)
Currently, the Indonesian Ministry of Education has implemented a new rule with every student expected to have an internship in the industry. With the aim of each student being able to understand the situation of the world of work so that preparation before completing a bachelor's degree is stronger. However, one of the problems found is that students cannot determine the placement of internships. This study tries to provide a solution to these problems by applying the rules from the head of the study program to provide recommendations to students. These rules are built based on student academic scores stored in the campus database which is controlled by the head of the study program. The method used is Distance from Average Solution (EDAS). The EDAS method is to determine the highest ranking using PDA is the positive distance from the average and (NDA) is the negative distance from the average. The results of this study provide recommendations automatically in the hope of supporting the current campus academic system.